PROFESI HUKUM DAN PROFESSIONAL DALAM BIDANG HUKUM - Nurul Hikam; Umi Yuniatin Maulidah; Andika Budi Wicaksono (JURNAL ILMIAH NUSANTARA, 2024)
Profession is a title or position where the person who holds it has special knowledge and knowledge that he or she has obtained through experience or even training, while Professional is concerned with the special skills that a person has to carry out a job. So the professionalism of law enforcers can be seen from the level of mastery of legal knowledge, skills and personality of law enforcers in carrying out their duties and authority in their work. Being fair is an obligation that the profession has when wrong practices occur in the profession. And a professional should not ignore the unethical actions of fellow professionals. This is part of carrying out the duties of a legal professional. So a professional has a code of ethics such as, Respecting the dignity of all professions, Increasing dedication to the profession, Adding quality, Determining standard standards for the profession, Improving the quality of the organization so that it becomes more trustworthy